2014
DOI: 10.1111/ssm.12072
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor Clusters: Characterizing Instructor Metaphorical Reasoning on Limit Concepts in College Calculus

Abstract: Novice students have difficulty with the topic of limits in calculus. We believe this is in part because of the multiple perspectives and shifting metaphors available to solve items correctly. We investigated college calculus instructors' personal concepts of limits. Based upon previous research investigating introductory calculus student metaphorical reasoning, we examined 11 college instructors' metaphorical reasoning on limit concepts. This paper focused on previous research of metaphor clusters observed am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It is known from the researchers' experiences that a source of cognitive difficulties for students is the limit concept (Denbel, 2014). Many students struggle with limits (Cappetta & Zollman, 2013;McCombs, 2014;Patel, McCombs & Zollman, 2014). Those researchers identified specific student difficulties with limits.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from the researchers' experiences that a source of cognitive difficulties for students is the limit concept (Denbel, 2014). Many students struggle with limits (Cappetta & Zollman, 2013;McCombs, 2014;Patel, McCombs & Zollman, 2014). Those researchers identified specific student difficulties with limits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cappetta and Zollman (2013) found that students have difficulties with understanding limits, involving the infinite processes of limits and the value of limits. Additionally, metaphorical reasoning, a way of understanding a situation to resolve disequilibrium that students encounter when faced with a new problem situation (Patel et al, 2014), develops without the knowledge of the lecturer and impedes students' understanding of mathematical concepts. A student who understands a mathematical concept can move between numerical, algebraic, graphical and application representations.…”
Section: Literature Reviewmentioning
confidence: 99%